Modelo de gestión administrativa para el sector de costura - Hidalgo Vinocunga, Miriam Alexandra (2017)
The objective of the research is to propose a model of administrative management that contributes to the improvement of organizational culture for small companies in the area of Sewing, this model is based on establishing the necessary steps to achieve an efficient management of both material and economic resources, for this reason, the administrative management model called Zero Based Budget was designed in order to establish programs which must be carried out in the planning, organization, direction and control, these ones allowed to assign roles to each area that makes up a small company such as: administration, finance, production, marketing and human talent, so as to arrange efficiently the functional organization chart and assign tasks appropriately. Small and medium companies (pymes) are considered as the sustainable economy of the country, representing an average of 80% of active businesses, among them the sewing sector generates a wide range of ready-made products, which according to the base of the Latacunga Fire Department business register corresponds to 0.52%, of the total of 59% of the small businesses that there is in the locality, sector is made up mostly of non-academically trained staff, because of this the owners do not implement a modern administration, being is a limit to maintain an efficient growth in the organizational development. The research methodology is based on a non-experimental qualitative and quantitative approach, with a descriptive research and an inductive method. This methodology is fundamental for the development of the project and its performance. With the implementation of the zero-based budget management model, the owners of small sewing companies will be more dynamic in achieving the goals and objectives and thus achieve greater sustainable development in productivity, profitability, competitiveness and an eminent organizational development. In addition, when the management model is implemented, small companies will become a dynamic entity of the economy and will maintain sustainable management of it. In other words it contributes to the development of the sector as well as to other sectors related to this one.